Hola,
Necesito despejar "L" en la siguiente fórmula: K = 5/3 ( L - 24 ).
También necesito despejar "K" en la siguiente fórmula: L = ![K = L_{0} [1+K(T- T_{0} )] K = L_{0} [1+K(T- T_{0} )]](https://tex.z-dn.net/?f=K+%3D+L_%7B0%7D+%5B1%2BK%28T-+T_%7B0%7D+%29%5D)
Gracias:3
Respuestas
Respuesta dada por:
17
K = 5/3 ( L - 24 )
3/5K = L - 24
L = 3/5K + 24
L = Lo[1 + K(T - To)]
L/Lo = 1 + K(T - To)
L/Lo - 1 = K(T - To)
K = [L/Lo - 1] / (T - To)
3/5K = L - 24
L = 3/5K + 24
L = Lo[1 + K(T - To)]
L/Lo = 1 + K(T - To)
L/Lo - 1 = K(T - To)
K = [L/Lo - 1] / (T - To)
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años